Long noncoding nature brain-derived neurotrophic factor antisense is associated with poor prognosis and functional regulation in non–small cell lung caner. Issue 5 (April 2017) - Shen, MingJing; Xu, Zhonghua; Jiang, Kanqiu; Xu, Weihua; Chen, Yongbin; Xu, ZhongHeng
In this study, we evaluated the prognostic potential and functional regulation of human nature antisense, brain-derived neurotrophic factor antisense, in non–small cell lung cancer. Non–small cell lung cancer carcinoma and adjacent non-carcinoma lung tissues were extracted from 151 patients. Their endogenous brain-derived neurotrophic factor antisense expression levels were compared by quantitative reverse transcription polymerase chain reaction. Clinical relevance between endogenous brain-derived neurotrophic factor antisense expression level and patients' clinicopathological variances or overall survival was analyzed. The potential of brain-derived neurotrophic factor antisense being an independent prognostic factor in non–small cell lung cancer was also evaluated. In in vitro non–small cell lung cancer cell lines, brain-derived neurotrophic factor antisense was upregulated through forced overexpression. The effects of brain-derived neurotrophic factor antisense upregulation on non–small cell lung cancer in vitro survival, proliferation, and migration were evaluated by viability, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide, and transwell assays. Brain-derived neurotrophic factor antisense is lowly expressed in non–small cell lung cancer carcinoma tissues and further downregulated in late-stage carcinomas. Brain-derived neurotrophic factor antisense downregulation was closely associated with non–small cell lung cancer patients' advanced tumor, lymph node, metastasis stage, and positive status of lymph node metastasis, and confirmed to be an independent prognostic factor for patients' poor overall survival. In non–small cell lung cancer A549 and H226 cell lines, forced overexpression of brain-derived neurotrophic factor antisense did not alter cancer cell viability but had significantly tumor suppressive effect in inhibiting in vitro non–small cell lung cancer proliferation and migration. Endogenous brain-derived neurotrophic factor antisense in non–small cell lung cancer carcinoma could be a potential biomarker for predicting patients' prognosis. Overexpressing brain-derived neurotrophic factor antisense may also have a therapeutic potential in inhibiting non–small cell lung cancer tumor growth.